Effects of Diosmin on Vascular Leakage and Inflammation in a Mouse Model of Venous Obstruction - Zou, Junjie; Yuan, Dongping; Yang, Jin; Yu, Yun (Frontiers in Nutrition, 2022)
Iliac vein compression syndrome (IVCS) plagues countless people. Severe iliac vein compression (IVC) leads to aggravation of inflammation and is closely related to left deep vein thrombosis (DVT). It has become a heavy economic and social burden on modern society. However, due to the limitations of animal models, the current IVCS-related research is limited, and its underlying mechanism remains to be further studied. Here, we generated a mouse model of iliac vein stenosis (IVS) to monitor the response of venous function to IVCS, such as vascular leakage and inflammation. Then, the clinically widely used bioactive ingredient diosmin was used to confirm the therapeutic effect in a mouse model. The results showed that in the IVCS mouse model, vascular leakage increased, and the expression of adhesion molecules and inflammatory factors increased. The impurities of diosmin can affect the metabolism of active ingredients, and it is unknown whether it has any effect on the treatment of venous diseases. Therefore, in this study, we studied the therapeutic difference between two different purity diosmin and verified the better effect of high-purity diosmin on venous dysfunction. In addition, we not only validated the potential of treating the IVCS mouse model as a stable and reproducible animal model for pathophysiological studies, but also provided new ideas for future venous disease prevention and treatment research, indicating a new treatment The strategy is used for venous diseases.